Global Antimicrobial Stewardship with a Focus on Low- and Middle-Income Countries: A position statement for the international society for infectious diseases. (July 2020) - Pierce, Jacob; Apisarnthanarak, Anucha; Schellack, Natalie; Cornistein, Wanda; Maani, Amal Al; Adnan, Syamhanin; Stevens, Michael P.
Highlights: ⬢ Global antimicrobial resistance is increasing. ⬢ Antimicrobial stewardship is critical for optimizing the safe and effective use of antimicrobials and for limiting antimicrobial resistance. ⬢ Low- to middle-income countries can effectively utilize antimicrobial stewardship but face unique challenges. ⬢ Key resources exist to help establish antimicrobial stewardship programs in low- to middle-income countries. Abstract: Antimicrobial resistance is a global public health crisis. Antimicrobial Stewardship involves adopting systematic measures to optimize antimicrobial use, decrease unnecessary antimicrobial exposure and to decrease the emergence and spread of resistance. Low- and middle-income countries (LMICs) face a disproportionate burden of antimicrobial resistance and also face challenges related to resource availability. Although challenges exist, the World Health Organization has created a practical toolkit for developing Antimicrobial Stewardship Programs (ASPs) that will be summarized in this article.